Development of Curved Three-Dimensional Shape Learning Media Ethnomathematics-Based Using Augmented Reality - Ira Ika Damayanti; Annisa Ayu; Umi Indah Sariah; Mustaqfiroh Mustaqfiroh; Intan Ayu Oktaviani; Farida Nursyahidah (Mathematics Dept, Math. and Science Faculty, Universitas Negeri Semarang, 2023)
A learning media is needed that can make abstract mathematics understandable and applicable in the real world where learning media currently does not interact much with technology.This study aims to develop learning media that uses Ethnomathematics-based Augmented Reality in the Gunungan tradition, which is valid, practical, and effective. The research subjects for the trial class are junior high school class IX students, with one class as a small class, one as a large class, and one as a control class. The learning media developed in this study is Augmented Reality (AR) assisted learning media with a combination of real and virtual objects in a real environment. Based on the results of descriptive analysis, it was found that the learning media developed had good quality because it met valid, practical, and effective criteria. The development of Augmented Reality-based spatial media can be used as a supporting medium for mathematics in grade 9 junior high school.Media pembelajaran diperlukan untuk membangun abstraksi agar matematika lebih mudah dipahami dan diterapkan dalam dunia nyata dimana media pembelajaran sata ini belum banyak berinteraksi dengan teknologi. Tujuan penelitian ini adalah untuk mengembangkan media pembelajaran yang menggunakan Augmented Reality berbasis Etnomatematika pada tradisi Gunungan yang valid, praktis dan efektif. Subyek penelitian untuk kelas uji coba adalah siswa kelas IX SMP, dengan satu kelas sebagai kelas kecil, satu kelas sebagai kelas besar, dan satu kelas sebagai kelas kontrol. Media pembelajaran yang dikembangkan dalam penelitian ini adalah media pembelajaran berbantuan Augmented Reality (AR) dengan perpaduan antara benda nyata dan maya dalam lingkungan nyata. Berdasarkan hasil analisis deskriptif diperoleh bahwa media pembelajaran yang dikembangkan berkualitas baik karena memenuhi kriteria valid, praktis, dan efektif. Pengembangan media augmented reality berbasis media dimensi tiga ini dapat digunakan sebagai media pendukung untuk pembelajaran matematika di kelas 9 SMP.